The Sta. Ana Ferry Terminal and Marina Complex - Ibanez, Alexei Gideon C. (College of Architecture, University of the Philippines Diliman, 2015)
The island garden city of Samal is one of the most highlighted tourist destinations of the Davao region and the presentation of the island's image is a key factor in promoting it's tourism. As a support for this cause, this study would like to concretely determine the destination image of Samal and use it as a foundation for the design of transport facilities used to serve tourists who may be interested in visiting or already bound for the island. The final product of this study is the translation of the destination image of Samal into a Ferry terminal complex which would positively affect the perception and travel experience of the tourists and parties who are interested in visiting the island.